The Sorcerer as Apprentice: his Notes (The computer in/and teaching the craft of composition) - Rea, John (Circuit)

(untitled) (Les Presses de l'Université de Montréal, 2008)
AbstractIn order to highlight some of the transformations in the practice of composition that occur due to the introduction of computing, the author provides two texts in a special typographical format which he calls ‘parallel processing’.An allegorical story entitled Wolf-URL together with ensuing texts that deal with interpretations of the allegory, particularly in a section entitled Updaters, Update Now!, attempt to put forward a critical apparatus for dealing with documentation (and underlying ideologies) related to an enquiry, with its non-exhaustive findings, that the author conducted during the spring of 2007 into the transformation of the craft of musical composition since the 1970s. They include musings about the relationship between professor and student composer where the computer plays or does not play a role in the teaching process. The outlines of this enquiry are located in a section entitled Setup Wizard; an assessment model is found in the Assessment Wizard.By means of this new print format, the reader will be able not only to speed up the reading experience and exchange valuable information between the multiple fragments, but will also be able to draw whatever implications seem fitting from the ongoing juxtaposition.